Komunikasi Kesehatan Mental untuk Menciptakan Kepuasan Pengguna Telemedicine - Diva Khautsar Dipraja; Kussusanti Kussusanti (Calathu: Jurnal Ilmu Komunikasi, 2024)
Communication through mobile apps is still looking for a better form, how to be carried out effectively, and how to be well received by the audience. One of the mobile apps widely used by the public today is telemedicine, which offers the integration of various health services. In health communications, the message sent by the doctor is proven to affect patient satisfaction. However, no studies on user satisfaction with telemedicine regarding mental health have been found. One telemedicine service in Indonesia is Halodoc, which provides psychological consultation and mental health articles. This study seeks to prove whether the quality of psychological consultation messages and mental health articles affects Halodoc user satisfaction. Concepts used are health communication, communication psychology, interpersonal communication, message quality, and customer satisfaction. With the quantitative method, this research sampling technique was purposive sampling. Questionnaires were distributed through Google Docs to 100 male and female respondents over 17 years old who had psychological consultations and read mental health articles through Halodoc in the last six months. With all the significant values being 0,000, this study finds out the effect of message in psychological consultation (0,461), mental health articles (0,469), and both together (0,560) on telemedicine user satisfaction.